2013
DOI: 10.3109/09513590.2013.819079
|View full text |Cite
|
Sign up to set email alerts
|

Age- and body mass index-related differences in the prevalence of metabolic syndrome in women with polycystic ovary syndrome

Abstract: The prevalence of Mets appears to be primarily determined by obesity and age whereas PCOS per se appears to be a less important contributing factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…However, the data of the RT-PCR analysis did not confirm the FOS downregulation in SCAAT from obese compared to lean. In addition to this, Chazenbalk et al [79] and Jones et al [80] have recently reported an underexpression of FOS and JUN in women with Polycystic Ovary Syndrome, a disease often accompanied by obesity [81,82], agreeing with our results found in young male subjects. Moreover, CITED2 a member of the cited family of nuclear regulators and NR3C1 were downregulated (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…However, the data of the RT-PCR analysis did not confirm the FOS downregulation in SCAAT from obese compared to lean. In addition to this, Chazenbalk et al [79] and Jones et al [80] have recently reported an underexpression of FOS and JUN in women with Polycystic Ovary Syndrome, a disease often accompanied by obesity [81,82], agreeing with our results found in young male subjects. Moreover, CITED2 a member of the cited family of nuclear regulators and NR3C1 were downregulated (Table 2).…”
Section: Resultssupporting
confidence: 93%
“…Metabolic syndrome for adults was defined by different criteria, for example 25 articles used the Adult Treatment Panel III (ATP III) and its modifications criteria . Six articles used the American Heart Association/National Heart Lung Blood Institute (AHA) and its modification criteria . Four articles used the World Health Organization (WHO) criteria .…”
Section: Resultsmentioning
confidence: 99%
“…In 15 Articles, 9,18,22,23,25,27,32,[36][37][38]40,46,[48][49][50] PCOS was defined by the National Institute of Health as the presence of two of three criteria of chronic anovulation, clinical and/or biochemical signs of hyperandrogenism with the exclusion of other etiologies. 51 Also, 27 articles 8,[13][14][15][16][18][19][20]24,26,[28][29][30][31][33][34][35][41][42][43][44][45][52][53][54][55][56] used the criteria of the European Society for Human Reproduction and Embryology/ American Society for Reproductive Medicine (ESHRE/ASRM) diagnostic criteria as two of the three criteria of hyperandrogenism, polycystic ovaries on ultrasound (PCO) and irregular anovulatory periods. 57 Four articles 8,18,39,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations